2018
DOI: 10.1073/pnas.1809753115
|View full text |Cite
|
Sign up to set email alerts
|

Haiti’s biodiversity threatened by nearly complete loss of primary forest

Abstract: Tropical forests hold most of Earth’s biodiversity. Their continued loss through deforestation and agriculture is the main threat to species globally, more than disease, invasive species, and climate change. However, not all tropical forests have the same ability to sustain biodiversity. Those that have been disturbed by humans, including forests previously cleared and regrown (secondary growth), have lower levels of species richness compared with undisturbed (primary) forests. The difference is even greater c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
57
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 20 publications
0
57
2
Order By: Relevance
“…Our research sets a baseline to help understand how species will respond to future habitat modification and climate change on Hispaniola. With extreme levels of habitat loss already fueling considerable extinction of amphibians and reptiles in the Haitian portion of Hispaniola (Hedges et al, ), it is more important than ever to survey any groups of Hispaniolan organisms to learn about their biology and begin to curtail the processes underlying their declines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research sets a baseline to help understand how species will respond to future habitat modification and climate change on Hispaniola. With extreme levels of habitat loss already fueling considerable extinction of amphibians and reptiles in the Haitian portion of Hispaniola (Hedges et al, ), it is more important than ever to survey any groups of Hispaniolan organisms to learn about their biology and begin to curtail the processes underlying their declines.…”
Section: Discussionmentioning
confidence: 99%
“…Our surveys took place on Hispaniola, a large Greater Antillean island comprising Haiti and the Dominican Republic. Given the extreme level of habitat loss in Haiti at all elevations, including evidence for ongoing species‐level extinction of vertebrates (Hedges et al, ), we chose a mountain range in nearby Dominican Republic to document ecological communities in a locality with relatively little current human impact. Essentially, all of the Sierra Martín García (SMG) is protected as a national park.…”
Section: Introductionmentioning
confidence: 99%
“…Deforestation on the nonbreeding grounds has been linked to declines of Wood Thrush (Hylocichla mustelina) in Central America (Taylor and Stutchbury 2016) and Golden-winged Warblers (Vermivora chrysoptera) in northern South America (Kramer et al 2018), but our annual apparent survival estimates are likely too imprecise to detect any comparable trend in apparent survival. With Haiti's primary forests now almost completely vanished (Hedges et al 2018), conservation of remaining broadleaf forests in the Dominican Republic take on additional significance for Bicknell's Thrush.…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis in Brazil's Atlantic Forest showed that an estimated 27–32 percent of the endemic species in this biome are currently committed to extinction (Strassburg et al., ). Haiti has lost all but 0.32 percent of its primary forest and is undergoing a mass extinction of its endemic biodiversity (Hedges, Cohen, Timyan & Yang, ). Restoration efforts can build on the conservation of small fragments or transformation of agricultural fields into young forests or agroforests.…”
Section: Introductionmentioning
confidence: 99%